RESPONSIBILITY ACCOUNTING INFORMATION SYSTEMS FOR ASSESSING PROFIT MANAGER PERFORMANCE - Octavia, Evi; Vera Monika, Utin; Belinda Ayu Putri, Alvita; Hasanah, Nur; Anbiya (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to determine how the application of the Responsibility Accounting Information System to assess the performance of profit center managers. Design/ methodology / approach: The research method used is descriptive method with a case study approach. Primary data obtained from questionnaires designed by researchers. Respondents are postal Employees who are in profit Center with the number of samples using the power analysis. Findings: the results of the study answer the problems that the manager’s profit target has not been achieved from period to period. Practical implications: The results of this study are expected to provide input for managers to consider the application of Responsibility accounting information systems. Originality / value: the uniqueness of this research is to examine the performance of the profit center at PT POS Indonesia